2019
DOI: 10.1186/s42358-019-0067-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific risk factors for gout: a systematic review of cohort studies

Abstract: Background: Though gout is more prevalent in men than women, it remains unclear whether gender influences risk factors for incident gout. We aimed to systematically review all cohort studies examining risk factors for the development of gout by gender. Methods: MEDLINE, EMBASE, CINAHL and the Cochrane Library were searched from inception to March 2019. Risk factors for gout examined were: age, ethnicity, consumption of alcohol, meat, seafood, dairy products, purine-rich vegetables, coffee and fructose, vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
2
15
0
5
Order By: Relevance
“…As a comparison, the prevalence of increasing uric acid levels in nutritional people is more than 2.98 times more than people with malnutrition and in obese people it is 5.96 times more than people with malnutrition [9]. Gout is 2.2 times more likely to occur in individuals with a body mass index ≥ 30 kg / m2 [2].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…As a comparison, the prevalence of increasing uric acid levels in nutritional people is more than 2.98 times more than people with malnutrition and in obese people it is 5.96 times more than people with malnutrition [9]. Gout is 2.2 times more likely to occur in individuals with a body mass index ≥ 30 kg / m2 [2].…”
Section: Resultsmentioning
confidence: 96%
“…Long-lasting hyperuricemia can cause chronic kidney disease with tubular changes. Hypertensive individuals were 1.64 (1.34-2.01) and 2.11 (1.64-2.72) times more likely to develop gout as a normotensive individual [2].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A third limitation is that we were unable to examine sex-specific effects of obesity on urate or gout. Globally, the prevalence of obesity is higher for women (15%) than men (11%) 49 , yet gout is more common in men 50 . A fourth limitation is that our findings are only applicable to those of European ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown varying results regarding the relationship between total testosterone and SU levels. Some studies have shown a positive association [ 11 , 12 , 13 , 14 ], and other studies have shown a negative association [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%